Validity of CSF alpha-synuclein to predict psychosis in prodromal Alzheimer's disease - Monge-García, Sonia; García-Ayllón, María-Salud; Sánchez-Payá, José; Gasparini-Berenguer, Ruth; Cortés-Gómez, María-Ángeles; Sáez-Valero, Javier; Monge-Argilés, José-Antonio (Frontiers in Neurology, 2023)
Background Alzheimer's disease (AD) accompanied by psychotic symptoms (PS) has a poor prognosis and may be associated with imbalances in key neural proteins such as alpha-synuclein (AS). Aim The aim of the study was to evaluate the diagnostic validity of AS levels in the cerebrospinal fluid (CSF) as a predictor of the emergence of PS in patients with prodromal AD. Materials and methods Patients with mild cognitive impairment were recruited between 2010 and 2018. Core AD biomarkers and AS levels were measured in CSF obtained during the prodromal phase of the illness. All patients who met the NIA-AA 2018 criteria for AD biomarkers received treatment with anticholinesterasic drugs. Follow-up evaluations were conducted to assess patients for the presence of psychosis using current criteria; the use of neuroleptic drugs was required for inclusion in the psychosis group. Several comparisons were made, taking into account the timing of the emergence of PS. Results A total of 130 patients with prodromal AD were included in this study. Of these, 50 (38.4%) met the criteria for PS within an 8-year follow-up period. AS was found to be a valuable CSF biomarker to differentiate between the psychotic and non-psychotic groups in every comparison made, depending on the onset of PS. Using an AS level of 1,257 pg/mL as the cutoff, this predictor achieved at least 80% sensitivity. Conclusion To our knowledge, this study represents the first time that a CSF biomarker has shown diagnostic validity for prediction of the emergence of PS in patients with prodromal AD.